Power Quality Improvement in Distribution System Connected Wind Turbine Using Static Synchronous Compensator. - Trinh , Trọng Chưởng (Journal of Technical Education Science, 2008)
Grid connected wind turbines may cause voltage quality problems, such as: reliability, voltage variation and flicker. This paper discusses the power quality improvement of grid connected wind turbine fixed-speed induction generator. A method to power quality improvement by using a voltage source converter (VSC) based STATCOM (Static Synchronous Compensator) is presented, which shows it is an efficient mean to improve voltage quality